2022
DOI: 10.1021/acsomega.1c05905
|View full text |Cite
|
Sign up to set email alerts
|

Azo-Linked Porous Organic Polymers for Selective Carbon Dioxide Capture and Metal Ion Removal

Abstract: The facile and environmentally friendly synthesis of porous organic polymers with designed polar functionalities decorating the interior frameworks as an excellent adsorbent for selective carbon dioxide capture and metal ion removal is a target worth pursuing for environmental applications. In this regard, two azo-linked porous organic polymers denoted man-Azo-P1 and man-Azo-P2 were synthesized in water by the azo-linking of 4,4′-diaminobiphenyl (benzidine) and 4,4′-methylenedianiline, respectively, with 1,3,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…In contrast to starting compounds, which provided sharp diffraction peaks, indicating they are crystalline solids, PXRD of all fourteen polymeric products displayed broad diffraction peaks, pointing to their amorphous nature with no long-range order. This agrees with the literature data available for similar azo-bridged polymers, which are also amorphous because of the irreversible formation of the azo bond [ 24 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast to starting compounds, which provided sharp diffraction peaks, indicating they are crystalline solids, PXRD of all fourteen polymeric products displayed broad diffraction peaks, pointing to their amorphous nature with no long-range order. This agrees with the literature data available for similar azo-bridged polymers, which are also amorphous because of the irreversible formation of the azo bond [ 24 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Resultssupporting
confidence: 92%
“…Triazine-based POPs, besides possessing high nitrogen content, also exhibit high chemical and thermal stability, making them one of the most promising materials for practical applications in this field. Furthermore, recent studies indicated that azo groups are particularly well-suited for design of POPs, which could be used for highly selective gas separations [ 24 , 26 , 27 , 28 , 29 , 30 , 31 ]. It was reported that azo-bridged POPs show excellent CO 2 /N 2 selectivity, which increases with rising temperature [ 24 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…10a) which can be attributed to the irreversible formation of azo bonds and is consistent with previous reports. 16,17,20,21,46–48 Thermogravimetric analysis showed that TPP-azo is thermally stable up to approximately 250 °C in N 2 atmosphere, when it begins to gradually lose mass (Δ m ∼ −3%) until about 440 °C, when it starts to decompose faster and shows another, greater, increase in the decomposition rate around 510 ° C (Fig. 10b).…”
Section: Resultsmentioning
confidence: 99%
“…11 As a result, POPs have gained increasing attention and have shown great potential. 12 POPs can be utilized for a variety of purposes, including applications in the fields of gas storage and adsorption, 13 separation, 14 heterogeneous catalysis, 15 energy conversion and storage, 16 drug delivery, 17 water treatment, 18 and so on. POPs can be classified into several types based on their synthesis route and structural features, e.g.…”
Section: Introductionmentioning
confidence: 99%